Discourse Analysis of Entrepreneurship School Ideology in the Education System - Ratna Dewi Pangestuti; Pamudi Handoyo; Farid Pribadi (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2021)
Current educational needs are required to adapt to global needs. The education system must be able to keep up with market demand. This has an impact on shifting educational ideology, including discourse in it. This study aims to uncover the discourse of entrepreneurship school at The Naff Elementary School Kediri, East Java. This study uses a qualitative method with a hermeneutic approach. This study uses Michel Foucault's theory of discourse analysis. The results of this study indicate that the discourse of entrepreneurship school has an impact on the education system with the ideology of capitalism behind it. The learning approach with the CTL or Contextual Teaching and Learning method is one form of revitalizing education based on the discourse of entrepreneurship school